Determination of genetic variation for vegetative and floral traits in African marigold (Tagetes erecta) - SINGH, KANWAR PAL; RAJU, D V S; NAMITA; JANAKIRAM, T (The Indian Journal of Agricultural Sciences, 2014)
Twenty-one genotypes of African marigold were (Tagetes erecta L.) evaluated for 11 growth and flowering related traits to study their genetic parameters such as variability, heritability, genetic (GCV), phenotypic (PCV) coefficient of variation and correlation and path coefficient analysis. Analysis of variance for all the traits showed significant differences among genotypes for all the growth and flowering related traits. High range in mean performance has been observed for traits, viz. plant height (64.00-106.67 cm), plant spread (49.33-72.00 cm), flower diameter (3.77- 6.17 cm), days required for flowering (78.67-99.33 days), number of secondary branches (22.13-37.47) and flower duration (26.00-44.83 days). Higher genotypic and phenotypic coefficient of variation was observed for traits such as fresh flower weight per plant, flower fresh weight per 10 flowers, number of flowers per plant, stem girth, flowering duration, etc. The high value (> 90%) of heritability was observed for all traits except plant height, plant spread and stem girth. The genetic advance was found ranged from 1.23 for flower diameter to 288.69 for fresh flower weight per plant. High values of genetic advance as per cent of mean was recorded for number of flowers (59.79%) followed by fresh flower weight per plant (59.32%) and flower fresh weight per 10 flowers (58.09%). Fresh flower weight per plant is significantly and positively correlated both at genotypic and phenotypic level for plant spread, flower fresh weight per flower, number of flowers per plant and flower diameter. Path coefficient analysis at genotypic level revealed that the number of primary branches per plant contributed highest and has significantly positive direct effect on fresh flower weight per plant followed by number of flowers per plant, flower diameter, flower fresh weight per flower, days required for flowering and stem girth. The different genotypes were identified to be performing differently for different quantitative traits. Hence, those genotypes with superior traits could be involved in the hybridization programme for assembling of desirable traits in a single genotype.